Antibacterial Activity of Papaya (Carica papaya L.) Seed Ethanol Extract against Staphylococcus aureus Isolated from Diabetic Ulcers - Diah Putri Aprilia; Hartalina Mufidah; Anas Fadli Wijaya (LPPM Universitas dr. Soebandi, 2025)
Background: Staphylococcus aureus is a bacterium that causes infections and is pathogenic to humans. Papaya (Carica papaya L.) seed extract contains various bioactive compounds, including tocopherols, terpenoids, flavonoids, alkaloids such as carpaine, and enzymes such as papain and lysozyme, which are known for their potential antimicrobial effects. Purpose: This study aimed to determine the antibacterial activity of papaya seed ethanol extract against S. aureus isolated from the foot ulcers of diabetic patients. Methods: An experimental quantitative study was conducted to evaluate the antibacterial activity of papaya seed ethanol extract at concentrations of 40%, 60%, and 80%. The extracts were prepared using the Ultrasonic-Assisted Extraction (UAE) method. Antibacterial activity was assessed by measuring the inhibition zones formed against S. aureus. Data were analyzed using a one-way ANOVA followed by a post hoc test to determine statistical significance. Results: The papaya seed extract exhibited concentration-dependent antibacterial activity against S. aureus. The mean inhibition zones were 0.00 mm at 40%, 15.07 mm at 60%, and 18.83 mm at 80%, whereas the positive control produced an inhibition zone of 46.36 mm. Conclusions: Papaya seed ethanol extract demonstrated antibacterial activity against S. aureus isolated from diabetic foot ulcers, with the strongest inhibition observed at the 80% concentration.